2019
DOI: 10.1371/journal.pone.0213672
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of arbuscular mycorrhizal fungi on nutrient uptake, N2 fixation, N transfer, and growth in a wheat/faba bean intercropping system

Abstract: Arbuscular mycorrhizal fungi (AMF) can play a key role in natural and agricultural ecosystems affecting plant nutrition, soil biological activity and modifying the availability of nutrients by plants. This research aimed at expanding the knowledge of the role played by AMF in the uptake of macro- and micronutrients and N transfer (using a 15N stem-labelling method) in a faba bean/wheat intercropping system. It also investigates the role of AMF in biological N fixation (using the natural isotopic abundance meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 56 publications
5
42
0
5
Order By: Relevance
“…Mean values of available K in soils were the highest in soils of the upper layer (Fig 3). The results obtained for available N, P, and K presented in Table 2 and Figs 1, 2, and 3 agree with the findings of Ingraffia et al, (2019) who found that AMF symbiosis improved the percentage of N derived from the atmosphere in the total N biomass of Faba bean grown in mixture (+20%) but not in pure sand. Nitrogen transfered from Faba bean soil to wheat soil was low (2.5-3.0 mg pot -1 ) and inoculation with AMF increased N transfer by 20% in terms of above-and below ground growth and uptake of nutrients.…”
Section: Resultssupporting
confidence: 89%
“…Mean values of available K in soils were the highest in soils of the upper layer (Fig 3). The results obtained for available N, P, and K presented in Table 2 and Figs 1, 2, and 3 agree with the findings of Ingraffia et al, (2019) who found that AMF symbiosis improved the percentage of N derived from the atmosphere in the total N biomass of Faba bean grown in mixture (+20%) but not in pure sand. Nitrogen transfered from Faba bean soil to wheat soil was low (2.5-3.0 mg pot -1 ) and inoculation with AMF increased N transfer by 20% in terms of above-and below ground growth and uptake of nutrients.…”
Section: Resultssupporting
confidence: 89%
“…Besides, mycorrhizae also excrete H + and low-molecular weight organic chelating compounds, such as citric acid, oxalic acid, and siderophores, to solubilize Fe in soil [151]. Recently, mycorrhizal inoculation in wheat roots was reported to have increased the uptake of P, Fe, and Zn by the plant, along with greater root length and density [44]. In maize, the symbiosis of mycorrhiza alters the expression patterns of three key iron homeostasis genes in sulfur-deprived plants, which indicates sulfur works as a signaling molecule for Fe homeostasis [152,153].…”
Section: Endophytes As the Emerging Participant Of Microbe-mediated Bmentioning
confidence: 99%
“…大田试验中, 米豆和玉米间作系统中米豆的固氮比例 增加最高可达121% [9] . 在盆栽试验中, 蚕豆/小麦间作 使蚕豆的固氮比例增加最高可达108% [10] . 也有30%左 右的研究表明, 间作对豆科作物固氮比例没有显著的…”
Section: 的研究表明间作会显著增加豆科作物的固氮比例 如unclassified
“…在豌豆/燕麦间作系统中, 间作豌豆固氮比例 降低13% [14] . 不同豆科作物在不同禾/豆间作体系中固 氮能力的巨大差异主要受到豆科作物本身的种类、根 系分泌物和丛枝菌根真菌等生物因素的影响 [10,15,16] , 其 次还会受到一些环境因子即土壤水分、土壤矿质营养 和土壤pH等非生物因素的限制 [17~19] . 为了挖掘间作系 统中豆科作物固氮潜力并应用于农业生产, 需要更好 地了解禾本科/豆科间作提高豆科作物共生固氮的 机理.…”
Section: 如在蚕豆/高粱间作系统中 间作蚕豆的固氮比例降低unclassified
See 1 more Smart Citation